A complex filter-based adaptive integral grid synchronisation algorithm for a PV system. Issue 4 (3rd July 2020) - Choudhury, Satish; Subudhi, Bidyadhar; Sharma, Renu
ABSTRACT: The issues such as deterioration of power quality owing to nonlinear loads, sudden changes in load demand, switch to dynamic loads, the occurrence of fault at the load or grid side is addressed using proposed DQ frame Complex Filter-based Adaptive Integral Algorithm (DCFAIA). The objective of the proposed control algorithm is to maintain the frequency at the desired level irrespective of electrical disturbances and also to remove the DC offset present in the synchronising parameters due to nonlinear load, lower the harmonic content in the grid parameters and maintain the power factor unity by compensating the reactive power. The performance of the proposed algorithm is compared with that of conventional algorithms such as Improved Second-Order Generalised Integrator (ISOGI), Third Order Generalised Integrator (TOGI), Least Mean Fourth (LMF). From the comparative assessment, it is observed that the proposed algorithm exhibits superior performance in terms of precision, settling time, steady and transient errors.